Multi-modal triggered-release sonodynamic/chemo/phototherapy synergistic nanocarriers for the treatment of colon cancer - Zhou, Yun; Gao, Yueyang; Yao, Nannan; Lu, Guozhi; Dong, Chuyu; Wang, Kexin; Zhang, Junfeng; Sun, Jing; Li, Ke; Li, Xueping (Frontiers in Bioengineering and Biotechnology, 2024)
Most colon cancer patients are diagnosed at an advanced stage, with a grim prognosis. In clinical, various combination therapies have been employed to enhance the efficacy of colon cancer treatment. The essence of combined treatment is the judicious selection and combination of various treatment units. Phototherapy (PT), sonodynamic therapy (SDT), and chemotherapy are treatment modalities that rely on the active molecules to treat tumors, and have been demonstrated to synergistically enhance tumor treatment efficacy. However, the differences in the metabolism of active molecules and hypoxic microenvironment of tumors have limited the synergistic effects of the aforementioned methods. To address this significant issue, in this study, we utilized polydopamine (PDA) as the encapsulated material to form a rigid shell that contains the therapeutic molecules IR-780 and methotrexate (MTX) on the surface of perfluorohexane (PFH) microdroplets through self-assembling method to develop an SDT/chemotherapy/PT combined nanoparticles (SCP NPs). Transmission electron microscopy (TEM) revealed that the nanoparticles exhibited a hollow shell structure, with an average size of approximately 100 nm. SCP NPs have excellent stability and biocompatibility in both in vitro and in vivo. The absorption and emission spectrum of the loaded IR-780 did not exhibit any significant shift, and the photothermal temperature rose to 92 ℃. Their ultrasonic cavitation effect was good and their cell inhibitory effect of MTX was maintained. SCP NPs can achieve multi-modal triggered release through ultrasound, laser irradiation, and pH, ensuring a simultaneous accumulation of therapeutic molecules in the tumor area and effectively alleviating tumor hypoxia. Additionally, both the near-infrared fluorescence (NIF) signal and the ultrasonic cavitation signal of the nanoparticles can be utilized for tracking and monitoring treatment efficacy. Most notably, SCP NPs exhibited outstanding synergistic treatment effects at low intervention levels, resulting in a 67% cure rate of tumors. These results provide an experimental basis for developing the new clinical treatments for colon cancer.